2014
DOI: 10.1002/tox.22028
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of di(2‐ethylhexyl) phthalate causes endocrine‐disruptive effects in marine medaka (Oryzias melastigma) embryos

Abstract: Di (2-ethylhexyl) phthalate (DEHP) is extensively distributed in marine environments. However, limited research on the toxicological and molecular effects of DEHP on marine organisms has been conducted. Our study investigated the accumulation, elimination, and endocrine-disruptive effects of DEHP on embryonic marine medaka (Oryzias melastigma). The medaka embryos were continuously exposed to DEHP (0.01, 0.1, and 1 mg/L) or 17β-estradiol (E2, 0.01 mg/L) until hatching, and the newly hatched larvae were then tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…In our study, PPAR γ was thought to transduce the toxicity of DEHP at 0.2–2 μ M in both primary cultured endometrial cells and endometrial adenocarcinoma cell line (ishikawa) [ 23 ]. We also obtained consistent results in a marine fish model where the expressions of PPAR γ and aromatase were both enhanced after fish embryo exposure to DEHP at 0.1–1 mg/L [ 24 ]. In vivo, DEHP is metabolized to mono(2-ethylhexyl) phthalate (MEHP) which could activate both PPAR α and PPAR γ and then suppress the transcription of aromatase and estradiol production in the ovary.…”
Section: Environmental Chemicals As Exogenous Ligandssupporting
confidence: 59%
“…In our study, PPAR γ was thought to transduce the toxicity of DEHP at 0.2–2 μ M in both primary cultured endometrial cells and endometrial adenocarcinoma cell line (ishikawa) [ 23 ]. We also obtained consistent results in a marine fish model where the expressions of PPAR γ and aromatase were both enhanced after fish embryo exposure to DEHP at 0.1–1 mg/L [ 24 ]. In vivo, DEHP is metabolized to mono(2-ethylhexyl) phthalate (MEHP) which could activate both PPAR α and PPAR γ and then suppress the transcription of aromatase and estradiol production in the ovary.…”
Section: Environmental Chemicals As Exogenous Ligandssupporting
confidence: 59%
“…Wang et al . reported that the accumulation of DEHP caused endocrine disruption in medaka embryos [ 22 ]. Zhai et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although present in surface waters in low concentrations BEHP, DBP and NP are posing possible health hazards, while they tend to accumulate in aquatic organisms (Wofford et al, 1981;Lee et al, 2015) and thus can reach the food chain through digestion of fish or when river water is used for irrigating of nearby fields. Published data show that BEHP, DBP, and NP or their metabolites in addition to the disruption of endocrine system (Kloas et al, 1999;Christen et al, 2011;Ye et al, 2016) induce genotoxic and even mutagenic effects (Phillips et al, 1982;Agarwal et al, 1985;Kleinsasser et al, 2001;Frassinetti et al, 2011).…”
Section: Determination Of Investigated Endocrine-disrupting Compoundsmentioning
confidence: 99%